PERANAN LEMBAGA PENGEMBANGAN MASYARAKAT AMUNGME DAN KAMORO (LPMAK) DALAM MENINGKATKAN SUMBER DAYA MANUSIA DI KABUPATEN MIMIKA PROPINSI PAPUA - ERAKIPIA, YOSEPH (Sam Ratulangi University, 2014)
Joint forces with global economics can be supposed by making state as company of public which its stockholder each and everyone anywhere reside in. The stockholder do not vote every four or five year but every hour, every day through tycoon of their house core. Globalization have eliminated traditional boundarys of sovereignty of state where capital shall no longger have national flag. Pursuant to idea background, hence writer feel to interest to take research discussion fundamental with emphasize at :